Thermal Stability and Drug-Excipient Compatibility Studies of Peppermint and Caraway Oils for Formulation of Chewable Tablets - K. Sachan, Nikhil; Pushkar, Seema; K. Sachan, Anupam; Ghosh, S.K. (Asian Journal of Chemistry, 2013)
Drug delivery is highly innovative in terms of materials to assist delivery, excipients and technology which allows release of drugs in a manner desired for improved therapeutic efficacy, safety and patient compliance. Among many other factors cost of non-compliance alone estimated to be ca. 13 % of total healthcare expenditure per year. Providing patients with simplified oral medications that will improve compliance and thus result more effective treatment has been one of the major drivers for innovation in the oral controlled drug delivery market. In this connection the oral chewable tablets were investigated as possible alternative formulations for the delivery essential oils known to be effective for the treatment of various ailments and have been administered traditionally as aromatic waters, elixirs, or more recently in the soft gelatin capsules. Now-a-days when people are increasingly taking several products as breath freshener, the present concept to formulate these essential oils in the form of chewable dosage forms so that these can be administered for such therapeutic uses and can provide simultaneously breath freshness to consumer in view of the urban lifestyle. This paper discuss the thermal stability and drug-excipient compatibility studies of peppermint and caraway oils for formulation of chewable tablets as alternative dosage form towards improved patient compliance and market viability.